PERAN PEMIMPIN DALAM MEMOTIVASI PEGAWAI TATA USAHA (STUDI PADA MTS NEGERI KOTO BARU, KABUPATEN SOLOK) - Amri, Amri (Graduate Program Magister Manajemen Pendidikan, 2016)
The aim of this qualitative research was to describe the role of principal in motivating the administration officers, and to understand the problems related to the policy of principal MTs Negeri Koto Baru Solok. The interview and documentation were used as instruments on collecting data. The results showed that the role of principal in motivating administration officers by upgrading personal relationship and understanding personal character. While the problems were the administration officers had different caharacter and different mindset.Â Keywords: Leader, Motivation, Aministration Officer, MTs Negeri Koto Baru, Kabupaten Solok.